Bionic absorbable composite bone implant and preparation method thereof
By using polymer raw materials and doped active ionic inorganic non-metallic materials in extrusion 3D printing, combined with plasma etching and directional freezing treatment of hydrogel precursors, the existing technology is solved. The problems of poor material strength and disordered structure have achieved high strength and toughness of bionic bone implants.
Patent Information
- Application Number
- CN202411773540.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing extruded 3D printing methods are difficult to obtain load-bearing and supportable materials with strong and bionic bone structure, resulting in microcracks and failures of implants when loaded or fatigued.
By mixing polymer raw materials with inorganic non-metallic materials doped with active ions, extruded 3D printing is used to form a composite morphology of oriented simulated collagen fibers and inorganic active bone salts, and through plasma etching and hydrogel precursors Directional freezing treatment forms a long-range and orderly porous structure, enhancing the mechanical strength and toughness of the material.
The long-range ordered structure of the material is achieved, which significantly improves the strength and toughness of the implant, can meet the material requirements of medical repair, and reduces poor interfacial compatibility and residual stress of the material, avoiding microcracks and failures.
Smart Images

Figure CN119424760A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical composite material processing, in particular to a bionic absorbable composite bone implant and a preparation method thereof. Background Art
[0002] Bone is a load-bearing and supportive material with strength and toughness that has evolved naturally to perfectly match the functions of the human body. It has characteristics that other materials cannot match. In bone tissue, collagen fibers and hydroxyapatite crystals are closely arranged. In the bone matrix of mature bone tissue, the collagen fibers are thin but regularly arranged in layers, with inorganic bone salts deposited on them. The collagen fibers are branched and often extend from one layer to another adjacent layer. They are intertwined to form a three-dimensional network structure that runs through the bone matrix. Hydroxyapatite crystals, as inorganic bone salts, are distributed in the collagen matrix in needle-like form, and their crystallization direction is distributed along the long axis of the collagen fibers. This interconnected three-dimensional structure and the composite interlayer of biologically active bone salts enable it to withstand multi-sided pressure, so that while having good osteogenic activity, the bone tissue has high compressive resistance and stability, effectively enhancing the support and toughness of the bone to meet the needs of human behavior and movement.
[0003] Patent application publication number CN103301511A discloses a composite implant for human bone fixation, which is mainly prepared by mixing polymers with inorganic non-metals such as polyamide 6 fiber, methyl methacrylate and N-vinyl pyrrolidone copolymer and hydroxyapatite powder, and preparing multiple raw materials by hot pressing to obtain the final product. Only through simple mechanical mixing, there is only a simple physical wrapping effect between the materials, and there is no interaction between chemical bonds or physical bonds. Patent application publication number CN116924426A discloses a method for regulating the distribution of silicon and aluminum in the molecular sieve framework and its products, wherein the silicon aluminum gel (sol) and pure silica gel (sol) are aged to a secondary gel state respectively, so that the silicon and aluminum atoms in the gel (sol) interact with the structure directing agent under the action of the mineralizer, and the structure is rearranged to produce short-range ordered structural units or crystallized embryos, but it can only form an ordered structure and composition in a very small area, and still presents a disordered state in the long range. There is an urgent clinical need to simulate the short-range ordered composite long-range ordered multi-level anisotropic structure of bone formation to obtain a better matching medical implant.
[0004] Compared with traditional material preparation technology, 3D printing technology can manufacture porous materials with complex geometric shapes, breaking through the shape restrictions of traditional manufacturing methods. Among them, extrusion 3D printing technology has the characteristics of simple technical principles and low cost. This technology uses slurry or molten material as the molding raw material, and extrude the material through an extruder with a fine nozzle, and then stacks it layer by layer for molding. After extrusion, it is bonded together with the previous layer of material and stacked layer by layer until the workpiece is completely formed. Due to the existence of directional extrusion mechanics, it can present the material orientation characteristics, which can be used to form an oriented arrangement similar to collagen fibers. However, during the molding process of extrusion 3D printing technology, there will be aging differences in the nozzle extruded material when constructing the structure. The nozzle discharges the material in a molten or slurry state during printing, and then solidifies. Its rheological properties change continuously over time. The aging differences are more obvious when preparing larger products by 3D printing, resulting in poor interface compatibility and residual stress between layers with different printing times due to differences in curing time and rheological properties. The interface deterioration effect is obvious, which will cause the final material and product to easily produce microcracks at the interface when subjected to static load or fatigue stress, and failure will occur even under smaller stresses. It is very difficult to use extrusion 3D printing to obtain the special structure of bionic bone and the corresponding strong and tough load-bearing and supportive materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of poor strength of bionic bone implants obtained by the existing extrusion 3D printing method, and to provide a bionic absorbable composite bone implant and a preparation method thereof.
[0006] The specific plan is as follows:
[0007] A method for preparing a bionic absorbable composite bone implant comprises the following steps:
[0008] S1: mixing an inorganic non-metallic material and a doped active ion to obtain an inorganic non-metallic material doped with active ions; mixing a polymer raw material with a solvent, stirring evenly to obtain a polymer solution, mixing the inorganic non-metallic material doped with active ions with the polymer solution and a hydrogel precursor, stirring evenly, and then partially volatilizing the solvent to prepare a 3D printing slurry;
[0009] S2: injecting the printing slurry into a 3D printing machine, performing 3D printing to prepare a bone implant semi-finished product, and then performing a drying process;
[0010] S3: placing the bone implant semi-finished product that has been dried in a plasma generator cavity to perform a plasma etching reaction;
[0011] S4: placing the semi-finished bone implant after the plasma etching reaction in a specific mold, wherein the specific mold includes a cold surface for contacting a cold source, and a heat preservation cover is arranged on a side of the cold surface away from the cold source, wherein the heat preservation cover has a containing space for carrying a liquid;
[0012] Adding the hydrogel precursor solution into the insulation sleeve to immerse the semi-finished bone implant, and then evacuating the specific mold process and keeping it in a vacuum for a period of time;
[0013] S5: After the heat preservation reaction is completed, the specific mold is translated onto a freezing table for specific orientation freezing treatment, and an ice template extending in a direction perpendicular to the cold surface is formed on the cold surface of the specific mold to achieve specific orientation molding of the hydrogel; then demolding is performed, and the obtained implant is freeze-dried to obtain the final composite bone implant.
[0014] Further, the inorganic non-metallic material is an inorganic artificial bone material, preferably one or more of hydroxyapatite, bioglass, β-TCP, and α-TCP;
[0015] Preferably, the doping active ions are one or more of Mg2+, Ca2+, Sr2+ ions;
[0016] Preferably, the doping active ions are added in the form of salt, and the amount of active metal ions added in the salt is 0.2-1.5% of the total weight of the inorganic non-metallic material, more preferably 0.5-1%.
[0017] Further, the polymer raw material is one or more of PCL, PLGA, and PLLA, and the addition amount of the polymer raw material is 5-80% of the total weight of the printing paste, preferably 10-40%;
[0018] Preferably, the solvent is one or more of chloroform, dimethyl sulfoxide, and tetrahydrofuran.
[0019] Further, the hydrogel precursor is one or more of collagen, polyvinyl alcohol, hyaluronic acid, gelatin, and sodium alginate, and the addition amount of the hydrogel precursor is 0.1-10% of the total weight of the printing slurry, preferably 1-8%;
[0020] Preferably, the solution of the hydrogel precursor in step S4 is an aqueous solution of the hydrogel precursor, and the concentration is preferably 1-50 wt %.
[0021] Furthermore, the 3D printing is performed by extrusion 3D printing; preferably, the extrusion rate is 1 to 5 mm / s, and a layer-by-layer printing method is adopted to obtain a bone implant semi-finished product of a certain thickness.
[0022] Furthermore, the plasma etching adopts a mixed gas intake mode of Ar and O2, preferably, the Ar intake flow rate is 5-50 ml / min, the O2 intake flow rate is 1-30 ml / min, and the etching time is 1-5 min.
[0023] Furthermore, in step S4, the bone implant semi-finished product is placed in a specific mold, and the specific orientation direction is a direction of height increase during 3D printing and the angle between the contact surface direction of the cold surface in the specific mold is between 75° and 105°.
[0024] Furthermore, the temperature of the vacuum insulation reaction in step S4 is 80-90° C., and the insulation time is 30-60 min.
[0025] The present invention also protects the bionic absorbable composite bone implant prepared by the preparation method of the bionic absorbable composite bone implant.
[0026] The present invention also protects the application of the bionic absorbable composite bone implant in the field of medical composite materials.
[0027] Beneficial effects:
[0028] The present invention can form a composite form of simulated collagen fibers and inorganic active bone salts with directional orientation by mixing polymer raw materials with inorganic non-metallic materials doped with active ions, and adopts an extrusion 3D printing method, which has the characteristics of bone tissue biomimetic. Among them, the polymer raw materials play the role of simulating bone fibers, and the inorganic non-metallic materials doped with active ions serve as bone salts distributed in bone tissue, together forming the main body of bone-like tissue.
[0029] Secondly, the present invention roughens the surface of the semi-finished product formed by 3D printing by plasma etching to form a nano-micromorphological surface, which is conducive to strengthening the mechanical microscopic locking and contact area of the material; at the same time, the activated surface formed by etching is more fully infiltrated with hydrogel by vacuum suction treatment in the hydrogel solution system (step S4 exhaust gas treatment), and the surface activation formed by plasma and the vacuum insulation treatment accelerate the reaction between the groups of the hydrogel at the interface and the groups of the printing surface, which can further promote the chemical bonding and cross-linking of the surface polymer material, inorganic non-metallic material and hydrogel, eliminating the problem of poor interface bonding of the above-mentioned different components after mixing. If conventional chemical etching is used, the acid-base neutralization reaction between the solution and the matrix material will accelerate the degradation of the matrix; after etching, the matrix is placed in the air, and the etched surface and the organic matter in the air undergo physical and chemical adsorption for a period of time, which will reduce the surface energy and surface activity, thereby significantly reducing the interface bonding force.
[0030] Again, the present invention adopts an extrusion 3D printing process, which is low in cost, but there are residual stresses between layers, and there is only physical interlocking between adjacent 3D printed ribs, resulting in low overall mechanical strength. In response to this problem, the hydrogel precursor used in the present invention can be oriented by directional freezing. Since the directional frozen hydrogel has orientation, the orientation direction is perpendicular to the height increase direction of the 3D printed substrate. By adding the reinforcing and toughening hydrogel fibers of the long chain segment structure, the locking between different layers in the height increase direction is increased, thereby obtaining a long-range ordered directional arrangement long-range ordered structure based on the short-range ordered mechanism formed in the ribs.
[0031] In summary, the preparation method of the bionic absorbable composite bone implant provided by the present invention accurately bionics the collagen fibers, inorganic substances and the bonding relationship between them in the human bone structure, forms fibers through polymer raw materials, interlocks with inorganic substances, and forms a directional arrangement at the same time, thereby obtaining a long-range ordered porous structure; on the other hand, the inner layer hydrogel in contact with the polymer fiber reacts chemically with the polymer fiber to form a chemical bond, and the outer layer hydrogel of the implant and the inner layer hydrogel undergo a cross-linking reaction through freezing to form an overall stable bonding effect, so that the bone implant has higher strength and better toughness, meeting the material requirements for medical repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings will be briefly introduced below. Obviously, the accompanying drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.
[0033] Figure 1 is a schematic structural diagram of a specific mold provided by an embodiment 1 of the present invention;
[0034] Figure 2 It is a physical photo of a specific mold provided in Example 1 of the present invention;
[0035] Figure 3 This is a surface morphology diagram of a composite bone implant provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The following are definitions of some terms used in the present invention. Other terms not mentioned here have definitions and meanings known in the art:
[0037] PCL: Polycaprolactone
[0038] PLLA: Poly(L-lactic acid)
[0039] PLGA: poly(lactic-co-glycolic acid)
[0040] TCP: Tricalcium phosphate, there are two main types used: α-TCP and β-TCP.
[0041] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.
[0042] Example 1
[0043] Weigh 50g of calcium chloride and 10g of magnesium chloride hexahydrate and add them to an aqueous solution to prepare an aqueous solution. Then, add 39.6g of diammonium hydrogen phosphate to the solution, adjust the pH value of the mixed solution to 11, and react at 60-80°C for 12h. After the reaction is completed, filter, separate, and wash to obtain a hydroxyapatite slurry doped with magnesium ions for use.
[0044] Weigh 4 g of the polymer raw material poly (L-lactic acid) PLLA and add it to 50 mL of chloroform. Stir in a sealed state for 4 hours to obtain a uniform solution. Then weigh 2 g of the prepared hydroxyapatite doped with magnesium ions and 0.5 g of the hydrogel precursor polyvinyl alcohol (PVA) powder and add them to the solution. After adding a small amount of surfactant, stir the slurry evenly and then put it in an oven to evaporate part of the solvent.
[0045] The prepared slurry was injected into a 3D printer for extrusion printing at an extrusion rate of 1.5 mm / s. A semi-finished bone implant of a certain thickness was obtained by layer-by-layer printing, and then placed in an oven for drying to constant weight. The semi-finished bone implant was transferred to a plasma generator chamber for plasma etching reaction, using a mixed gas of Ar and O2, wherein the Ar intake flow rate was 10 ml / min, the O2 intake flow rate was 5 ml / min, and the etching time was 5 min.
[0046] Immediately after etching, the semi-finished implant is transferred into a specific mold, such as Figure 1 As shown, the specific mold includes a cold surface for contacting a cold source, such as a heat-conducting metal sheet; a heat-insulating sleeve is arranged on the side of the cold surface away from the cold source, and the heat-insulating sleeve has a containing space for carrying liquid and implants.
[0047] The actual photo of the specific mold used in this embodiment is as follows Figure 2, using aluminum foil as the cold surface, the aluminum foil wraps a hollow cylinder from the bottom to form a heat-insulating sleeve structure. The cylinder is a polytetrafluoroethylene (Teflon) heat-insulating sleeve, and the hollow part in the center of the cylinder is used to contain liquid and implants. After the implant is placed, the top of the cylinder can be closed, and the aluminum foil is tightly fitted to the cylindrical sleeve by means of vacuum operation to form a sealed reaction system.
[0048] In this embodiment, the orientation direction of the implant semi-finished product placed in the insulation sleeve is 90° with the height increase direction during the 3D printing process and the angle with the cold surface contact surface direction. Then, a 10wt% hydrogel precursor aqueous solution of the same type is poured into the mold to immerse the implant semi-finished product, and then placed in a vacuum box with a set temperature of 80°C and evacuated to a vacuum degree of -0.09MPa, and then the pressure is released to normal pressure. This is repeated 3 times and kept warm for 60 minutes.
[0049] The processed composite bone implant and the mold are then moved to a low-temperature freezing table, with the bottom aluminum foil in contact with the cooling sheet (i.e., cold source), and frozen for 24 hours. During the freezing process, multiple ice templates parallel to the inner wall of the insulation sleeve are formed at the bottom of the accommodating space, such as Figure 1 As shown. The specific mold is surrounded by a polytetrafluoroethylene (Teflon) insulation sleeve, and aluminum foil is laid on the hollow bottom to provide a cold surface, and an ice template will be formed on the aluminum foil surface. The formation principle of the ice template is: because the temperature of the cold surface in contact with the cold source is very low, the temperature of the solution close to the cold surface decreases, and there will be a temperature gradient between the top and bottom of the solution. The water in the hydrogel precursor aqueous solution will slowly grow into an ice template along the contact surface perpendicular to the cold surface, thereby guiding the material to form a long-range ordered structure.
[0050] After demoulding the composite bone implant, place it in a freeze dryer and dry it for 24 hours to obtain the final composite bone implant.
[0051] Surface topography analysis of composite bone implants, such as Figure 3 As shown, it can be seen that the composite bone implant has a regular and orderly pore structure. This orderly pore is distributed in layers throughout the implant, that is, it is ordered in the long range. At the same time, the pores of each layer are basically the same size, parallel to each other, and arranged at equal intervals. The pores of the composite bone implant are rectangular holes with a length of about (0.3-0.5) mm and a width of about (0.2-0.4) mm, which perfectly meets the structural requirements of bionic bone.
[0052] The composite bone implant was placed under a load pressure of 5kg for 15 seconds, and the composite bone implant structure was not damaged and surface cracks did not occur, indicating that its strength and toughness can meet the requirements for medical use.
[0053] Example 2
[0054] Weigh 50g of calcium chloride and 13.3g of strontium chloride hexahydrate and add them to an aqueous solution to prepare an aqueous solution. Then add 39.6g of diammonium hydrogen phosphate to the solution, adjust the pH value of the mixed solution to 11, and react at 60-80°C for 12h. After the reaction is completed, filter, separate and wash to obtain a strontium ion-doped hydroxyapatite slurry for use.
[0055] Weigh 4.5 g of the polymer raw material poly (L-lactic acid) PLLA and add it to 60 mL of chloroform. Stir in a sealed state for 4 hours to obtain a uniform solution. Then weigh 2.5 g of the prepared hydroxyapatite doped with magnesium ions and 0.8 g of the hydrogel precursor polyvinyl alcohol (PVA) powder and add them to the solution. After adding a small amount of surfactant, stir the slurry evenly and then put it into an oven to evaporate part of the solvent.
[0056] The prepared slurry was injected into a 3D printer for extrusion printing at an extrusion rate of 1.5 mm / s. A semi-finished bone implant of a certain thickness was obtained by layer-by-layer printing, and then placed in an oven for drying to constant weight. The semi-finished bone implant was transferred to a plasma generator chamber for plasma etching reaction, using a mixed gas of Ar and O2, wherein the Ar intake flow rate was 10 ml / min, the O2 intake flow rate was 5 ml / min, and the etching time was 5 min.
[0057] The etched semi-finished implant is immediately transferred to a specific mold, and the specific mold is the same as in Example 1. The orientation direction of the semi-finished implant is the height increase direction during the 3D printing process and the angle with the cold surface contact surface direction is 80°. Then, a 10wt% hydrogel precursor aqueous solution of the same type is poured into the mold to immerse the semi-finished implant, and then placed in a vacuum box set at 80°C and evacuated to a vacuum degree of -0.09MPa, and then the pressure is released to normal pressure, and this is repeated 3 times and kept warm for 60 minutes.
[0058] The processed composite bone implant and the mold were then moved horizontally to a low-temperature freezing table, with the bottom aluminum foil in contact with a cooling sheet (i.e., a cold source), and the freezing treatment was performed for 24 hours.
[0059] After demoulding the composite bone implant, place it in a freeze dryer and dry it for 24 hours to obtain the final composite bone implant, which has a regular and orderly pore structure. This orderly pore is distributed in layers throughout the implant, that is, it is ordered in the long range. At the same time, the pores of each layer are basically the same size, parallel to each other, and arranged at equal intervals. The pores of the composite bone implant are rectangular holes with a length of about (0.3-0.5) mm and a width of about (0.2-0.4) mm, which perfectly meets the structural requirements of bionic bone.
[0060] The composite bone implant was placed under a load pressure of 5kg for 15 seconds, and the composite bone implant structure was not damaged and surface cracks did not occur, indicating that its strength and toughness can meet the requirements for medical use.
[0061] Example 3
[0062] 40 g of 45S5 bioglass doped with 1% Sr prepared by a melting method was weighed, ball-milled in a ball mill, and then sieved, washed and dried to obtain bioglass powder for later use.
[0063] Weigh 6 g of polymer raw material PLGA and add it to 80 mL of chloroform. Stir in a sealed state for 4 hours to obtain a uniform solution. Then weigh 3 g of the prepared Sr-doped 45S5 bioactive glass and 1 g of hydrogel precursor sodium alginate and add them to the solution. After adding a small amount of surfactant, stir the slurry evenly and then put it in an oven to evaporate part of the solvent.
[0064] The prepared slurry was injected into a 3D printer for extrusion printing at an extrusion rate of 3.0 mm / s. A bone implant semi-finished product of a certain thickness was obtained by layer-by-layer printing, and then placed in an oven for drying to constant weight. The above-mentioned bone implant semi-finished product was transferred to the plasma generator cavity for plasma etching reaction, using a mixed gas of Ar and O2, wherein the Ar intake flow rate was 8 ml / min, the O2 intake flow rate was 6 ml / min, and the etching time was 6 min.
[0065] The etched implant semi-finished product is immediately transferred to a specific mold, and the specific mold is the same as in Example 1. The implant semi-finished product is placed in an orientation direction in which the height increase direction during the 3D printing process is at an angle of 100° to the cold surface contact surface direction, and then a 15wt% hydrogel precursor aqueous solution of the same type is poured into the mold to immerse the implant semi-finished product, and then placed in a vacuum box set at 80°C and evacuated to a vacuum degree of -0.09MPa, and then depressurized to normal pressure, and this is repeated 3 times and kept warm for 60 minutes.
[0066] The processed composite bone implant and the mold were then moved horizontally to a low-temperature freezing table, with the bottom aluminum foil in contact with a cooling sheet (i.e., a cold source), and the freezing treatment was performed for 24 hours.
[0067] After demoulding the composite bone implant, place it in a freeze dryer and dry it for 24 hours to obtain the final composite bone implant, which has a regular and orderly pore structure. This orderly pore is distributed in layers throughout the implant, that is, it is ordered in the long range. At the same time, the pores of each layer are basically the same size, parallel to each other, and arranged at equal intervals. The pores of the composite bone implant are rectangular holes with a length of about (0.3-0.4) mm and a width of about (0.2-0.3) mm, which perfectly meet the structural requirements of bionic bone.
[0068] The composite bone implant was placed under a load pressure of 5kg for 15 seconds, and the composite bone implant structure was not damaged and surface cracks did not occur, indicating that its strength and toughness can meet the requirements for medical use.
[0069] Example 4
[0070] Weigh 50g of calcium chloride and 13.3g of strontium chloride hexahydrate and add them to an aqueous solution to prepare an aqueous solution. Then add 39.6g of diammonium hydrogen phosphate to the solution, adjust the pH value of the mixed solution to 11, and react at 60-80°C for 12h. After the reaction is completed, filter, separate and wash to obtain a strontium ion-doped hydroxyapatite slurry for use.
[0071] Weigh 6.5 g of the polymer raw material PLGA and add it to 80 mL of chloroform. Stir in a sealed container for 4 hours to obtain a uniform solution. Then weigh 4 g of the prepared strontium ion-doped hydroxyapatite and 0.6 g of the hydrogel precursor gelatin and add them to the solution. After adding a small amount of surfactant, stir the slurry to make it uniform, and then put it in an oven to evaporate part of the solvent.
[0072] The prepared slurry was injected into a 3D printer for extrusion printing at an extrusion rate of 1.5 mm / s. A semi-finished bone implant of a certain thickness was obtained by layer-by-layer printing, and then placed in an oven for drying to constant weight. The semi-finished bone implant was transferred to a plasma generator chamber for plasma etching reaction, using a mixed gas of Ar and O2, wherein the Ar intake flow rate was 10 ml / min, the O2 intake flow rate was 5 ml / min, and the etching time was 5 min.
[0073] The etched implant semi-finished product is immediately transferred to a specific mold, and the specific mold is the same as in Example 1. The implant semi-finished product is placed in an orientation direction in which the height increase direction during the 3D printing process is at an angle of 95° to the cold surface contact surface direction, and then a 10wt% hydrogel precursor aqueous solution of the same type is poured into the mold to immerse the implant semi-finished product, and then placed in a vacuum box set at 80°C and evacuated to a vacuum degree of -0.09MPa, and then depressurized to normal pressure, and this is repeated 3 times and kept warm for 60 minutes.
[0074] The processed composite bone implant and the mold were then moved horizontally to a low-temperature freezing table, with the bottom aluminum foil in contact with a cooling sheet (i.e., a cold source), and the freezing treatment was performed for 24 hours.
[0075] After demoulding the composite bone implant, place it in a freeze dryer and dry it for 24 hours to obtain the final composite bone implant, which has a regular and orderly pore structure. This orderly pore is distributed in layers throughout the implant, that is, it is ordered in the long range. At the same time, the pores of each layer are basically the same size, parallel to each other, and arranged at equal intervals. The pores of the composite bone implant are rectangular holes with a length of about (0.4-0.5) mm and a width of about (0.3-0.4) mm, which perfectly meet the structural requirements of bionic bone.
[0076] The composite bone implant was placed under a load pressure of 5kg for 15 seconds, and the composite bone implant structure was not damaged and surface cracks did not occur, indicating that its strength and toughness can meet the requirements for medical use.
[0077] Example 5
[0078] Weigh 50g of calcium chloride and 10g of magnesium chloride hexahydrate and add them to an aqueous solution to prepare an aqueous solution. Then, add 39.6g of diammonium hydrogen phosphate to the solution, adjust the pH value of the mixed solution to 11, and react at 60-80°C for 12h. After the reaction is completed, filter, separate, and wash to obtain a hydroxyapatite slurry doped with magnesium ions for use.
[0079] Weigh 4.5 g of polymer raw material PCL and add it to 50 mL of dimethyl sulfoxide. Stir in a sealed state for 4 hours to obtain a uniform solution. Then weigh 2.2 g of the prepared hydroxyapatite doped with magnesium ions and 0.6 g of hydrogel precursor polyvinyl alcohol PVA powder and add them to the solution. After adding a small amount of surfactant, stir the slurry evenly and then put it in an oven to evaporate part of the solvent.
[0080] The prepared slurry was injected into a 3D printer for extrusion printing at an extrusion rate of 5.0 mm / s. A semi-finished bone implant of a certain thickness was obtained by layer-by-layer printing, and then placed in an oven for drying to constant weight. The semi-finished bone implant was transferred to a plasma generator chamber for plasma etching reaction, using a mixed gas of Ar and O2, wherein the Ar intake flow rate was 12 ml / min, the O2 intake flow rate was 6 ml / min, and the etching time was 3 min.
[0081] The etched implant semi-finished product is immediately transferred to a specific mold, and the specific mold is the same as in Example 1. The implant semi-finished product is placed in an orientation direction in which the height increase direction during the 3D printing process is at an angle of 85° to the cold surface contact surface direction, and then a 20wt% hydrogel precursor aqueous solution of the same type is poured into the mold to immerse the implant semi-finished product, and then placed in a vacuum box set at a temperature of 90°C and evacuated to a vacuum degree of -0.09MPa, and then depressurized to normal pressure, and this is repeated 3 times and kept warm for 30 minutes.
[0082] The processed composite bone implant and the mold were then moved horizontally to a low-temperature freezing table, with the bottom aluminum foil in contact with a cooling sheet (i.e., a cold source), and the freezing treatment was performed for 24 hours.
[0083] After demoulding the composite bone implant, place it in a freeze dryer and dry it for 24 hours to obtain the final composite bone implant, which has a regular and orderly pore structure. This orderly pore is distributed in layers throughout the implant, that is, it is ordered in the long range. At the same time, the pores of each layer are basically the same size, parallel to each other, and arranged at equal intervals. The pores of the composite bone implant are rectangular holes with a length of about (0.3-0.4) mm and a width of about (0.2-0.3) mm, which perfectly meet the structural requirements of bionic bone.
[0084] The composite bone implant was placed under a load pressure of 5kg for 15 seconds, and the composite bone implant structure was not damaged and surface cracks did not occur, indicating that its strength and toughness can meet the requirements for medical use.
[0085] Comparative Example 1
[0086] Referring to Example 1, 50 g of calcium chloride and 10 g of magnesium chloride hexahydrate were weighed and added to an aqueous solution to prepare an aqueous solution, and then 39.6 g of diammonium hydrogen phosphate was added to the solution, and the pH value of the mixed solution was adjusted to 11. The mixture was reacted at 60-80° C. for 12 h. After the reaction was completed, the mixture was filtered, separated, and washed to obtain a hydroxyapatite slurry doped with magnesium ions for use.
[0087] Weigh 4 g of the polymer raw material poly (L-lactic acid) PLLA and add it to 50 mL of chloroform. Stir in a sealed state for 4 hours to obtain a uniform solution. Then weigh 2 g of the prepared hydroxyapatite doped with magnesium ions and 0.5 g of the hydrogel precursor polyvinyl alcohol (PVA) powder and add them to the solution. After adding a small amount of surfactant, stir the slurry evenly and then put it in an oven to evaporate part of the solvent.
[0088] The prepared slurry was injected into a 3D printer for extrusion printing at an extrusion rate of 1.5 mm / s. A semi-finished bone implant of a certain thickness was obtained by layer-by-layer printing, and then placed in an oven for drying to constant weight. The semi-finished bone implant was transferred to a plasma generator chamber for plasma etching reaction, using a mixed gas of Ar and O2, wherein the Ar intake flow rate was 10 ml / min, the O2 intake flow rate was 5 ml / min, and the etching time was 5 min.
[0089] The bone implant prepared above was then placed in a freeze dryer for 24 hours to obtain the final composite bone implant. After staying under a load pressure of 5 kg for 15 seconds, the bone implant structure was destroyed and surface cracks appeared.
[0090] Although Comparative Example 1 contains the hydrogel precursor PVA, it is not subjected to directional freezing and the orientation of the hydrogel cannot be exerted. The material has a long-range disorder problem in the structure, so the strength and toughness are significantly reduced, which is manifested as structural destruction and surface cracks under pressure.
[0091] Comparative Example 2
[0092] Referring to Example 1, 50 g of calcium chloride and 10 g of magnesium chloride hexahydrate were weighed and added to an aqueous solution to prepare an aqueous solution, and then 39.6 g of diammonium hydrogen phosphate was added to the solution, and the pH value of the mixed solution was adjusted to 11. The mixture was reacted at 60-80° C. for 12 h. After the reaction was completed, the mixture was filtered, separated, and washed to obtain a hydroxyapatite slurry doped with magnesium ions for use.
[0093] Weigh 4 g of the polymer raw material poly (L-lactic acid) PLLA and add it to 50 mL of chloroform. Stir in a sealed state for 4 hours to obtain a uniform solution. Then weigh 2 g of the prepared hydroxyapatite doped with magnesium ions and add it to the solution. After adding a small amount of surfactant, stir the slurry to make it uniform, and then put it into an oven to evaporate part of the solvent.
[0094] The prepared slurry was injected into a 3D printer for extrusion printing at an extrusion rate of 1.5 mm / s. A semi-finished bone implant of a certain thickness was obtained by layer-by-layer printing, and then placed in an oven for drying to constant weight. The semi-finished bone implant was transferred to a plasma generator chamber for plasma etching reaction, using a mixed gas of Ar and O2, wherein the Ar intake flow rate was 10 ml / min, the O2 intake flow rate was 5 ml / min, and the etching time was 5 min.
[0095] The etched semi-finished implant is immediately transferred to a specific mold, and the specific mold is the same as in Example 1. The orientation direction of the semi-finished implant is the height increase direction during the 3D printing process and the angle with the cold surface contact surface direction is 90°, and then the aqueous solution is poured into the mold to immerse the semi-finished implant, and then placed in a vacuum box with a set temperature of 80°C and evacuated to a vacuum degree of -0.09MPa, and then the pressure is released to normal pressure, and this is repeated 3 times and kept warm for 60 minutes.
[0096] The processed composite bone implant and mold are then translated to a low-temperature freezing table, the bottom aluminum foil is in contact with the cooling plate (i.e., cold source), and the freezing treatment is performed for 24 hours. After the composite bone implant is demoulded, it is placed in a freeze dryer and dried for 24 hours to obtain the final composite bone implant. The porous structure of the implant is not regularly distributed. After staying under a load pressure of 5kg for 15 seconds, the bone implant structure will be destroyed and surface cracks will appear.
[0097] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0098] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0099] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a bionic absorbable composite bone implant, characterized in that: The following steps are involved: S1: mixing an inorganic non-metallic material and a doped active ion to obtain an inorganic non-metallic material doped with active ions; mixing a polymer raw material with a solvent, stirring evenly to obtain a polymer solution, mixing the inorganic non-metallic material doped with active ions with the polymer solution and a hydrogel precursor, stirring evenly, and then partially volatilizing the solvent to prepare a 3D printing slurry; S2: injecting the printing slurry into a 3D printing machine, performing 3D printing to prepare a bone implant semi-finished product, and then performing a drying process; S3: placing the bone implant semi-finished product that has been dried in a plasma generator cavity to perform a plasma etching reaction; S4: placing the semi-finished bone implant after the plasma etching reaction in a specific mold, wherein the specific mold includes a cold surface for contacting a cold source, and a heat preservation cover is arranged on a side of the cold surface away from the cold source, wherein the heat preservation cover has a containing space for carrying a liquid; Adding the hydrogel precursor solution into the insulation sleeve to immerse the semi-finished bone implant, and then evacuating the specific mold process and keeping it in a vacuum for a period of time; S5: After the heat preservation reaction is completed, the specific mold is translated onto a freezing table for specific orientation freezing treatment, and an ice template extending in a direction perpendicular to the cold surface is formed on the cold surface of the specific mold to achieve specific orientation molding of the hydrogel; then demolding is performed, and the obtained implant is freeze-dried to obtain the final composite bone implant.
2. The method for preparing the bionic absorbable composite bone implant according to claim 1, characterized in that: The inorganic non-metallic material is an inorganic artificial bone material, preferably one or more of hydroxyapatite, bioglass, β-TCP, and α-TCP; preferably, the doped active ion is Mg 2+ , Ca 2+ , Sr 2+ One or more types of ions; Preferably, the doping active ions are added in the form of salt, and the amount of active metal ions added in the salt is 0.2-1.5% of the total weight of the inorganic non-metallic material, more preferably 0.5-1%.
3. The method for preparing the bionic absorbable composite bone implant according to claim 1, characterized in that: The polymer raw material is one or more of PCL, PLGA, and PLLA, and the addition amount of the polymer raw material is 5-80% of the total weight of the printing paste, preferably 10-40%; Preferably, the solvent is one or more of chloroform, dimethyl sulfoxide, and tetrahydrofuran.
4. The method for preparing the bionic absorbable composite bone implant according to claim 1, characterized in that: The hydrogel precursor is one or more of collagen, polyvinyl alcohol, hyaluronic acid, gelatin, and sodium alginate, and the amount of the hydrogel precursor added is 0.1-10% of the total weight of the printing slurry, preferably 1-8%; Preferably, the solution of the hydrogel precursor in step S4 is an aqueous solution of the hydrogel precursor, and the concentration is preferably 1-50 wt %.
5. The method for preparing the bionic absorbable composite bone implant according to claim 1, characterized in that: The 3D printing is performed by extrusion 3D printing; preferably, the extrusion rate is 1 to 5 mm / s, and a layer-by-layer printing method is adopted to obtain a semi-finished bone implant of a certain thickness.
6. The method for preparing the bionic absorbable composite bone implant according to claim 1 or 5, characterized in that: The plasma etching adopts a mixed gas intake mode of Ar and O2, preferably, the Ar intake flow rate is 5-50 ml / min, the O2 intake flow rate is 1-30 ml / min, and the etching time is 1-5 min.
7. The method for preparing the bionic absorbable composite bone implant according to claim 1, characterized in that: In step S4, the bone implant semi-finished product is placed in a specific mold, and the specific orientation direction is the angle between the height increase direction during the 3D printing process and the contact surface direction of the cold surface in the specific mold is between 75° and 105°.
8. The method for preparing the bionic absorbable composite bone implant according to claim 1 or 7, characterized in that: The temperature of the vacuum insulation reaction in step S4 is 80-90° C., and the insulation time is 30-60 min.
9. The bionic absorbable composite bone implant prepared by the method for preparing the bionic absorbable composite bone implant according to any one of claims 1 to 8.
10. Application of the bionic absorbable composite bone implant according to claim 9 in the field of medical composite materials.
Citation Information
Patent Citations
Complex implant for fixing human skeletons
CN103301511A
Method for regulating and controlling distribution of silicon and aluminum in molecular sieve framework and product thereof
CN116924426A
Preparation method of bionic artificial bone with multistage [micrometer / nanometer] pore structure
CN103462729A
Method for manufacturing three-dimensional bone tissue engineering bracket through extruding deposited 3D printing
CN108297396A
Method for preparing bionic laminar articular cartilage / bone compound implant
CN1961975A